An updated patent review of p38 MAP kinase inhibitors (2014-2019). (2nd June 2020) - Haller, Vanessa; Nahidino, Philipp; Forster, Michael; Laufer, Stefan A.
ABSTRACT: Introduction : During the first half of the last decade the p38 MAP kinase family was a very popular target in academic as well as industrial research programs. Many attempts to achieve marketing authorization for a p38 MAPK inhibitor for the treatment of pro-inflammatory diseases, like rheumatoid arthritis (RA), failed at the state of clinical trials, mostly due to selectivity and/or toxicity issues. Areas covered : Herein, the patents and corresponding publications of international companies, universities and other research institutions, which focus on the development, identification and optimization of new selective p38 inhibitors and their fields of use are summarized. Expert opinion : p38 MAP kinase inhibitors are a mature field with many pre-clinically validated structural classes, more than 20 candidates in clinical trials but still (except the weak and unselective p38 inhibitor pirfenidone) no approved drug. Big Pharma hasn't contributed much to the patents of the last five years but remarkable contribution have come from academic environment or small biotech companies. Three general punchlines of innovation have shown up. Tailor-made molecules with properties for local application, mainly type-II (Urea-type) inhibitors for lung- or skin diseases, isoform p38γ, δ-selective inhibitors for the treatment of cutaneous t-cell lymphoma (CTCL) and substrate-specific inhibitors (e.g. p38/MK2).